Analisis Cacat Produk Green Tyre dengan Pendekatan Seven Tools - Joko Hardono; Hendra Pratama; Andi Friyatna (Universitas Serang Raya, 2019)
Quality is one aspect that needs to be maintained in increasing consumer confidence and minimizing production costs. A motorcycle tire manufacturing company has a production defect of 5028 during February 2018. This study aims to reduce the number of defective products in the green tire cooking process in the curing area. The methods used in this study are seven tools, especially Pareto diagrams, and fishbone diagrams and analyzed the cause is 5W1H. Of the six types of green tire defects, under cure is the most dominant factor (40%) that causes disability. The improvement in Pneumatic Problems which the problem of under cure is human factors, machinery, and the method of being able to reduce defects by 48% from 891 pieces in February to 463 pieces in May. The decrease in defects in pneumatic problems affects the reduction in the number of defects in green tire products from 5206 pieces in February to 4699 pieces in May.